Culinary Learning Using Virtual Reality Based on Gamification Method - Winanti Winanti; Nurasiah; Beby Tiara; Erick Fernando; Sucipto Basuki; Riyanto (Politeknik Pertanian Negeri Samarinda, 2024)
Culinary is a promising business and food is a basic need for human life. Many people fall ill due to improper diet. Since the emergence of Covid-19 a few years ago, most people tend to be careful in maintaining their diet, and awareness of healthy food has increased. Significantly, learning with virtual reality-based gamification in post-pandemic conditions, many people prefer digital learning. To increase creativity, motivation, innovation, and student involvement and ultimately open many businesses in the food sector, fun learning is needed with interesting content with virtual reality-based gamification scenarios. Ease of learning will have an impact on improving culinary learning outcomes. The purpose of this study is to learn using virtual reality-based gamification methods to increase student creativity in determining recipes, choosing the right ingredients, and using the right cooking utensils. Increase student learning motivation, and create innovation in the culinary field, from combining recipes to attractive presentations. Student involvement and its output is the creation of technopreneurs in the culinary field, considering that culinary is the backbone of a country's economy and is a promising business